Precision Engineered Graphene Oxide Membranes Optimizing Thin Film Composite Layers for Solvent and Dye Separation - Widakdo, Januar; Fadly Azril Priodani; Hannah Faye M. Austria; Tsung Han-Huang; Aditya Rianjanu; Canggih Setya Budi; Anawati Anawati; Wei-Song Hung (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Organic solvent nanofiltration (OSN) is a promising separation technology with low energy consumption and environmental benefits. However, membrane stability in harsh organic solvents remains a challenge. Graphene oxide (GO) is widely explored due to its exceptional mechanical strength and selective permeability; however, further modifications are necessary to optimize its performance. This study investigates the enhancement of GO membranes by incorporating a thin-film composite (TFC) layer through interfacial polymerization using polyethyleneimine (PEI) and trimethyl chloride (TMC). The fabricated membranes were characterized for theirmorphology, chemical structure, and filtration performance using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), X-ray Photoelectron Spectroscopy (XPS), and contact angle measurements. Filtration tests were conducted with ethanol and Congo red dye solutions. The optimized membrane, composed of 0.1 wt% PEI 800 Mw and 0.05 wt% TMC, exhibited superior performance, demonstrating a permeance of 8.06 ± 2.31 L L m-2 h-1 bar-1 and a rejection rate of 95.20 ± 1.54% for Congo red dye. Additionally, the membrane exhibited a charge-dependent separation mechanism, achieving a 98.64 ± 0.38% rejection of methyl green due to both affinity and Donnan effects. These findings provide insights into developing advanced OSN membranes for efficient solvent purification and dye separation.